Sustentabilidade em pequenas empresas inovadoras : um estudo com os casos de sucesso do programa Agentes Locais de Inovação em Sergipe entre 2016 e 2018 - Costa, Margareth de Souza (2020)
Sustainable innovation or innovation oriented to sustainability has been understood as an innovation that generates renewal or improvement of products or services in the short and long term, in order to improve the economic, environmental and social performance of companies. To this end, this research aimed to understand how the innovations implemented by companies participating in the ALI program incorporated innovation management practices oriented towards sustainability, according to the Sustainable Innovation Cube model. Specifically, it was a question of identifying the elements of integration of the sustainability criteria present in the innovations adopted, analyzing the integration of stakeholders in the innovation process, understanding how the service content in the products supplied increased, verifying how the adoption of the marketing aimed at sustainable innovation, investigating the ways of raising awareness of sustainability adopted by companies and analyzing the connections between innovation and sustainability in these companies. As for the methodological procedures, the research has a qualitative nature. The strategy used was the method of studying multiple cases, considering in the analysis the companies participating in the ALI program between 2016 and 2018 and which were successful cases in Sergipe. To this end, data were collected through documentary research and semi-structured interviews. It is worth mentioning that the content analysis was used for the data treatment. In addition, the interview information was inserted and interpreted with the aid of the IRAMUTEQ software. The results showed that the companies participating in the research implemented different innovations that culminated in the proposal of sustainable innovation. Finally, the findings of the cases indicate that the innovations implemented by small companies also contribute to understanding the theme of sustainable innovation, as addressed in the Sustainable Innovation Cube model.